Continuous intrathecal baclofen delivery in severely disabling spasticity - Simsek, Hakan; Zorlu, Emre; Bakal, Omer; Akarsu, Selim; Senol, Mehmet Güney (Vojnosanitetski pregled, 2021)
Background/Aim. Spasticity is the consequence of several clinical conditions including cerebral palsy, brain injury, spinal cord injury, multiple sclerosis, aneurysm bleeding, and some other neurological disorders. The aim of this study was to determine the efficacy of intrathecal baclofen (ITB) treatment in medically intractable severely disabling spasticity and present the challenges encountered during pump implantation surgery on these patients. Methods. The patients who underwent intrathecal baclofen pump implantation surgery between the years 2012 and 2015 with minimum follow-up of six months were recruited from the clinic archives. Twenty two patients with severe spasticity who had Modified Asworth Spasticity Scale (MASS) score of 3 or 4 were enrolled in our series. Eight of twenty-two patients were at pediatric age and they all were non-ambulant before surgery. Results. All of the patients underwent programmable intrathecal baclofen pump implantation surgery. Catheters were placed via percutaneous technique into to the subarachnoid space in 18 patients while, we had to perform partial hemi-laminectomy in order to place the catheters in 4 patients. All the patients improved significantly and 5 began using upper extremities and 3 adults became ambulant following physical therapy. Mean of the MASS scores improved from 3.59 to 1.32 (p < 0.001). Conclusion. The ITB therapy obviously increased quality of life and functional outcome in patients with disabling spasticity. As a result, physical treatment was more useful for these patients. Although some spinal abnormalities due to spasticity may necessitate partial hemilaminectomy to implant the pump, patients with intractable spasticity should be given the chance of intrathecal baclofen treatment at the earliest period of their lifetime disability.